2020
DOI: 10.1016/j.jobcr.2020.04.007
|View full text |Cite
|
Sign up to set email alerts
|

A review of the anticancer activity of Azadirachta indica (Neem) in oral cancer

Abstract: Background: Azadirachta indica (neem), belongs to the family of Meliaceae plants, is found in the Indian subcontinent. The neem tree is colloquially referred to as the village pharmacy due to its array of biological properties. Every part of the neem tree like its bark, leaves, sap, fruit, seeds, and twigs find a multitude of uses. It is customary to use them for management of skin diseases and various other infections. The anticancer properties of neem have been studied in the past and these include its abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 20 publications
0
16
0
2
Order By: Relevance
“…PCNA (proliferating cellular nucleic antigen) protein and it is identified their expression pattern are the main mechanism of all carcinoma, has major role in proliferation process acts as cell proliferative marker. PCNA expression pattern leaked higher amount in oral tissues particular literatures found expressed in oral cancer 28 . Up regulation of PCNA by treatment kirenol with DMBA painted hamsters proceeded to suppress cell multiplication and their communications by cell cycle arrest, this supports suggested that kirenol prevent the tumor formation oral administered in DMBA induced hamsters by cell cycle arrest.…”
Section: Discussionmentioning
confidence: 58%
“…PCNA (proliferating cellular nucleic antigen) protein and it is identified their expression pattern are the main mechanism of all carcinoma, has major role in proliferation process acts as cell proliferative marker. PCNA expression pattern leaked higher amount in oral tissues particular literatures found expressed in oral cancer 28 . Up regulation of PCNA by treatment kirenol with DMBA painted hamsters proceeded to suppress cell multiplication and their communications by cell cycle arrest, this supports suggested that kirenol prevent the tumor formation oral administered in DMBA induced hamsters by cell cycle arrest.…”
Section: Discussionmentioning
confidence: 58%
“…G1/S phase cell cycle arrest is associated with autophagy cell death following apoptosis [ 53 ]. Aqueous neem leaf extract is reported to have chemopreventive effects by regulating the enzymatic breakdown of glutathione in the oral mucosa [ 54 ].…”
Section: Plants With Beneficial Effects Against Oral Cancermentioning
confidence: 99%
“…Nimbolide is a type of limonoid derived from Azadirachta indica (neem tree) that inhibits the proliferation of carcinogenic cells by inducing apoptosis. The aqueous extract of neem leaves regulates the enzymatic breakdown of glutathione and thereby exerts an anticarcinogenic effect in the oral mucosa [ 54 ]. In a recent study, the chemopreventive use of nimbolide against SCC4 and EAhy926 oral cancer cell lines was analysed.…”
Section: Phytoextracts/phytoconstituents For the Treatment Of Oral Cancermentioning
confidence: 99%
“…They have also been reported to demonstrate inhibition of Akt protein and modulation of the Akt/mTOR pathway (Nitulescu et al, 2018;Srivastav et al, 2020). The anti-neoplastic properties of Azadirachta indica (neem) have been reported (Agrawal et al, 2020), it is been shown to modulate the tumor microenvironments, attenuate the proliferation of tumor cells (Agrawal et al, 2020).…”
Section: Backg Rou N Dmentioning
confidence: 99%